2015
DOI: 10.1111/anu.12374
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of female and male clams (Ruditapes philippinarum): energy intake and temperature reliance

Abstract: We analysed the effect of temperature, coupled with food ingestion rate (IR), on the fatty acid (FA) profile of female and male clams conditioned in two groups: L (low IR at 14 and 18°C) and H (high IR at 18 and 22°C). Significant differences for group L, both 18L and 14L with low IR and slow gonadal development, owed to differences in energy balance between 18L clams (negative energy balance) and 14L clams (positive energy balance). Plasmalogens (DMA 18:0) and non-methylene-interrupted FAs might protect again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(173 reference statements)
1
6
0
Order By: Relevance
“…The observed positive correlation between PUFAs content and the quantity of ingested planktons in this study further suggested that a variation in fatty acids contents during different gonad development stages was closely related to the fatty acid contents of planktons [27]. The high content of the gonadal PUFAs during the advanced gametogenesis stages of P. viridis was due to the increased ingestion of plankton, particularly Bacillariophyceae and dinoflagellates, which contain higher amounts of n-3 fatty acids [76,77]. More precisely, it was reported that Bacillariophyceae are rich in eicosapentanoic acid (EPA), while dinoflagellates (Pyrrophyceae) are enriched with docosahexaenoic acid (DHA) [76,77].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The observed positive correlation between PUFAs content and the quantity of ingested planktons in this study further suggested that a variation in fatty acids contents during different gonad development stages was closely related to the fatty acid contents of planktons [27]. The high content of the gonadal PUFAs during the advanced gametogenesis stages of P. viridis was due to the increased ingestion of plankton, particularly Bacillariophyceae and dinoflagellates, which contain higher amounts of n-3 fatty acids [76,77]. More precisely, it was reported that Bacillariophyceae are rich in eicosapentanoic acid (EPA), while dinoflagellates (Pyrrophyceae) are enriched with docosahexaenoic acid (DHA) [76,77].…”
Section: Discussionsupporting
confidence: 67%
“…The high content of the gonadal PUFAs during the advanced gametogenesis stages of P. viridis was due to the increased ingestion of plankton, particularly Bacillariophyceae and dinoflagellates, which contain higher amounts of n-3 fatty acids [76,77]. More precisely, it was reported that Bacillariophyceae are rich in eicosapentanoic acid (EPA), while dinoflagellates (Pyrrophyceae) are enriched with docosahexaenoic acid (DHA) [76,77]. In our study, it was revealed that during the gonadal mature stages, P. viridis consumed more than two times the amount of Bacillariophyce and Pyrrophyceae compared to that during the spent and resting stages (see Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids, including PUFA, are provided by microalgae, the primary food source to bivalves, and the amount of these compounds may vary with microalgae species (Rivero-Rodríguez et al, 2007). It is widely accepted that PUFA derive mainly from microalgae diet (Langdon and Waldock, 1981) because bivalves have a limited capacity to synthesize them (Ehteshami et al, 2011;Fernández-Reiriz et al, 2017). Thus, the nutritional value of the diet is often determined by the amount of PUFA, such as EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…EPA and DHA are considered two of the most important EFA required to gametogenesis (Ehteshami et al, ), being that higher accumulation of EPA in females has been suggested to be related to oocyte maturation and release during spawning while greater levels of DHA in males have been suggested to be involved in the synthesis of the spermatocyte membrane (Fernández‐Reiriz et al, ). Dridi and Romdhane () showed that FA content varied significantly during a whole year of analysis and showed a negative and significant correlation with the gametogenic condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that although several studies have been already dedicated to the lipid fraction of some of the selected products—namely clams of Ruditapes philippinarum sp. [ 21 , 22 , 23 ], oysters of Ostrea edulis sp. and Crassostrea gigas [ 21 , 24 ], octopuses of Octopus vulgaris sp.…”
Section: Introductionmentioning
confidence: 99%